MEMPERKUAT RESPONSIVITAS PENYELENGGARAAN PATEN DI KECAMATAN SAMARINDA ULU - Tri Wahyuni (Jurnal Administrative Reform, 2021)
Community satisfaction in the public service process conducted by the government is very important. The principle of community satisfaction in Samarinda Ulu District is represented by the implementation of the Community Satisfaction Survey (SKM) which is routinely carried out every year, using 9 (nine) elements. This study aims to analyze efforts to strengthen the responsiveness of the implementation of PATEN in Samarinda Ulu District. The survey guidelines apply to the Minister of Administrative Reform and Bureaucratic Reform Regulation No. 14 of 2017. This research is a descriptive study (description). The research approach is carried out using a qualitative approach. In general, the Community Satisfaction Survey (SKM) conducted by the District of Samarinda Ulu, has referred to the guidelines as stated in the Permanpan No. 14 of 2017. However, there are several things from the provisions as stated in Permenpan No. 14 of 2017 has not been followed up perfectly in its implementation, including related to an explanation of the implementation of activities, completeness of survey forms, survey analysis, inventory of service complaints, and follow-up planning.Keywords: public service, community satisfaction, survey